Postacute-Stroke Management Problems in Home Care Service: A Qualitative Single-Centered Study in Yogyakarta, Indonesia - Paryono, Paryono; Ar Rochmah, Mawaddah; Setyopranoto, Ismail; Trisnantoro, Laksono (Scientific Scholar, 2022)
Objective This study explores the postacute-stroke management problems, particularly for patients with total dependency (Barthel Index <20), in home care service of Dr. Sardjito Hospital (SH) from the hospital personnel's and caregiver's points of view.